y+54+9=0

Subtract 9 from both sides of the equation.

y+54=-9

To remove the radical on the left side of the equation, raise both sides of the equation to the power of 4.

y+544=(-9)4

Multiply the exponents in ((y+5)14)4.

Apply the power rule and multiply exponents, (am)n=amn.

(y+5)14⋅4=(-9)4

Cancel the common factor of 4.

Cancel the common factor.

(y+5)14⋅4=(-9)4

Rewrite the expression.

(y+5)1=(-9)4

(y+5)1=(-9)4

(y+5)1=(-9)4

Simplify.

y+5=(-9)4

Raise -9 to the power of 4.

y+5=6561

y+5=6561

Subtract 5 from both sides of the equation.

y=6561-5

Subtract 5 from 6561.

y=6556

y=6556

Exclude the solutions that do not make y+54+9=0 true.

No solution

Solve for y fourth root of y+5+9=0